Prioritizing sub-watersheds for soil and water conservation via morphometric analysis and the weighted sum approach: A case study of the Geba river basin in Tigray, Ethiopia. Issue 12 (December 2022) - Godif, Gebremedhin; Manjunatha, B.R.
Abstract: Ranking watersheds according to their susceptibility to soil erosion is crucial in setting priorities for soil and water conservation initiatives. The main intention of this work is to characterize and prioritize 12-sub-watersheds of the Geba River Basin, northern Ethiopia for planned soil and water conservation practices. SRTM-DEM, GIS, and statistical correlation-based weighted sum approach have been utilized for generating morphometric parameters, data processing, and calculating the combined rank of sub-watersheds respectively. Fourteen morphometric parameters that have high nexus with the soil erosion susceptibility were selected and quantified using different standardized mathematical equations. Based on these quantified variables, a compound factor (rank) was calculated for each sub-watershed. Using the combined rank, the sub-watersheds were clustered into five soil erosion susceptibility zones, i.e., very high, high, moderate, low, and very low. Results revealed that sub-watersheds 7, 8, 9, and 12 which collectively cover the majority of the area (36 % of the total area) are possibly fall under the very high soil erosion susceptibility. The high (comprising of sub-watersheds 1, 5, 11), moderate (consisting of sub-watersheds 2, 3), low (consisting of sub-watershed 10), and very low (consisting of sub-watersheds 4, 6) soil erosion susceptibility zones cover 26%, 28%, 4%, and 6% of the total area respectively. The results further reflect that sub-watersheds in the very high soil erosion susceptibility category require immediate action for implementing soil and water conservation measures. This study's findings could serve as a basis for policymakers and planners in the development of erosion control strategies. Abstract : Remote sensing; River basin; GIS; Sub-watershed.